PREVALENCIA DE CISTICERCOSIS PORCINA EN LA AMPLIACIÓN DEL PARQUE PORCINO DE VENTANILLA "PAMPAS DE LOS PERROS': CALLAO - Turín S., Rocío (2005)
Porcine cysticercosis is a zwnotic parasitic disease caused by Cysticercus celiulosae, the larval stage of the tapeworm Taenia solium. Cysticercosis is eudemic in Peru with a bigh prevalence in the mountains, jungleand the noahem coast; however, there is scarce infomation about its presence in Lima. The objective of the present study was to determine the seropreyalence of porcine cysticercosis in the expansion area of the Porcine Park "Pampas de los Perros" in Ventanilla district, Callao. A total of 299 serum samples collected from pigs in sectors A, B, C, D and E of the expansion area of the Porcine Park were tested by the Westem Blot iest. The corrected seroprevalence was 19-t 4%, and the rcai prevalence ohtaincd through a stochastic simulation beáa binomial test was 7%- There was a significant sbtistical difference (p<0.05) betwcen animals older than 12 montbs and the other age groups (<4,4-8, and >8-12 months), but none behveen sectors or sex. Anirnals older than 12 months of age and sectors A and B were found to be risk factors by the logistic regression test for the presence of cysticercosis in pigs @<0.05)